Steroidal arylidene hybrids with phenolic moieties: Integrated in silico, DFT, and electrochemical evaluation for therapeutic targeting - Qaoud, Mohammed T.; Capan, Irfan; Saydam, Sinan; Servi, Suleyman (Elsevier, 2026)
Targeting dual modulators of androgen biosynthesis enzymes, two phenol-substituted steroidal arylidene analogs-Dehydroepiandrosterone-Fn (DHEA-Fn) and Pregnenolone-Fn (PREG-Fn), where Fn denotes a phenolic moiety-were structurally characterized and comprehensively evaluated through a multidisciplinary approach integrating spectroscopic, electrochemical, and in silico analyses. Advanced Nuclear Magnetic Resonance (NMR) techniques, including two-dimensional heteronuclear correlation (2D-HETCOR) NMR, confirmed E/Z isomerism in DHEA-Fn and supported precise assignment of regiochemical and stereoelectronic features. Structure-guided molecular docking and molecular mechanics-generalized Born surface area (MM-GBSA) calculations predicted favorable binding to 5 alpha-reductase type 2 and CYP17A1, positioning the compounds as potential dual inhibitors relevant to prostate cancer therapy. DHEA-Fn exhibited a superior docking profile (-10.53 kcal/mol) compared to the positive control Finasteride. Density functional theory (DFT) calculations indicated narrow HOMO-LUMO energy gaps and high electron affinity values, supporting enhanced redox reactivity and antioxidant potential. Electrochemical characterization using cyclic and square wave voltammetry confirmed quasi-reversible redox behavior consistent with the conjugated arylidene-phenol framework. This conjugated arylidene-phenol is proposed to act as a redox-active structural motif (i.e., a moiety capable of reversible electron transfer), potentially influencing bioactivation, oxidative stability, and interactions with redox-sensitive biological targets. In silico ADMET (absorption, distribution, metabolism, excretion, and toxicity) modeling further predicted excellent oral bioavailability, blood-brain barrier permeability, and no violations of drug-likeness rules. Distinct P-glycoprotein interaction profiles suggest variable CNS efflux, which may influence neuroactivity and systemic distribution. Together, the integration of electrochemical analysis and in silico modeling provides a predictive, mechanism-oriented framework for evaluating the therapeutic viability of steroidal scaffolds. These findings highlight DHEA-Fn and PREG-Fn as rationally designed, multifunctional candidates with favorable physicochemical, electronic, and pharmacological profiles for further development in androgen-related oncology.
Keywords: Steroidal arylidene hybrids; Phenolic pharmacophore; Dual enzyme inhibition; 5 alpha-reductase; CYP17a1; Redox pharmacology; DFT; Electrochemical analysis; Admet profiling; Prostate cancer